The local government officials' understanding of corruption in Dr Kenneth Kaunda District Municipality - Sekoto, Mohau Relebogile Miracle (My University, 2015)
Post-apartheid South Africa has faced numerous new challenges. Amongst these challenges is public sector corruption, which is pervasive and of major concern in the local sphere of government. The purpose of this study was to explore what the understanding of corruption is among local government officials in the Dr Kenneth Kaunda District Municipality. An investigation through interviews was conducted to gather the understanding of corruption by the officials. One of the major findings of the research was that corruption was generally comprehended as non-adherence and non-compliance to the set standards, procedures, policies and Acts passed to govern local government from National Government. Furthermore, local government officials were aware of anti-corruption policies but opted for non-compliance and non-adherence. It was also established that small salaries, social class competition and greed were amongst the motivating factors to corruption and that the main barrier to reporting corruption was fear of victimization at the workplace.
Keywords: Political corruption ;Local government -- Corrupt practices -- South Africa.